Socialization and Education on The Benefits of Probiotics for Children's Health in Primary School Until Senior High School Students in Tanjung Morawa - Cintya, Henni; Rimayani, Lisda; Syahputra, Hafid (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Dysbiosis is a condition in which there is an imbalance in the number of microorganisms in the human digestive tract. This condition often occurs in children. An imbalance in the number of microorganisms in the digestive tract in humans (microflora) occurs when bacterial overgrowth. This can cause infection or inflammation localized in the intestine which has the potential to cause various diseases. However, knowledge about probiotics is still not understood by the public. This community service activity aims to provide knowledge about the role of probiotic microorganisms for children's health, especially for elementary-high school children in Tanjung Morawa District. This Community Service activity was carried out by means of a lecture method by disseminating the activity plan to the children of the Yayasan Pauly Mandiri, then a demonstration by conducting counseling and displaying animated videos related to the socialization that was carried out. Community service activities in general received a very good response and high enthusiasm from students, and several teachers who attended as well as the chairman of the Pauly Mandiri Education Foundation in Kec. Tanjung Morawa asked to continue. The results of community service, especially practicing drinking probiotic drinks. The enthusiasm of the participants hopes that this outreach activity can be resumed regarding the manufacture of food or drinks containing probiotics so that children can apply them daily, and consume them to increase body immunity in the midst of a pandemic.